EFFECT OF MELATONIN AND SHORTENED DAYLIGHT ON THE REPRODUCTIVE PERFORMANCE OF JORDANIAN GOATS DURING THE OUT-BREEDING SEASON - M. KH. Al-Smadi; M. A. Alnimer; M. A. Abedal-Majed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study investigated the impact of melatonin (MEL) and a short photoperiod on the reproductive performance of local Jordanian goats during the out-breeding season. Forty-five nursing does and five bucks were divided into five groups: MEL with sponge (MS), MEL without sponge (M), darkness with sponge (DS), darkness without sponge (D), and a control group (C). The darkness groups were subjected to a 63-day controlled darkness program to simulate decreasing daylight hours. MEL was administered via subcutaneous implants, and the MS and DS groups received progesterone (P4)-impregnated sponges. The results showed that MEL levels significantly increased (P=0.007) in all experimental groups (MS, M, DS, and D) compared to the control group. The MS group exhibited the highest P4 levels (P=0.001). While there were no significant differences in estrus or conception rates among the groups, the MS group had the highest pregnancy rate at days 21 and 28. Fertilization rates were similar across all groups. Fecundity was comparable, but prolificacy was highest in the MS group. Hormonal treatments and reduced daylight influenced the bucks’ scrotal circumference, with the MS group displaying the largest (p<0.05) scrotal circumference and the highest testosterone concentration. In conclusion, the study suggests that administering MEL to goats, particularly in combination with P4 sponges, may enhance their reproductive capacity during the out-breeding season.